Summer is Coming! Join the Game of Timers Competition to Win Epic Prizes. Registration is Open. Game starts Mon July 1st.

It is currently 21 Jul 2019, 12:42

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Senior RC Moderator
User avatar
V
Status: ----__----___-----____-----
Joined: 02 Nov 2016
Posts: 3075
Location: Pakistan
GPA: 3.39
If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =  [#permalink]

Show Tags

New post Updated on: 12 Dec 2018, 01:33
1
1
00:00
A
B
C
D
E

Difficulty:

  15% (low)

Question Stats:

78% (01:03) correct 22% (01:20) wrong based on 72 sessions

HideShow timer Statistics


If \(a - b = \frac{a^2 - b^2}{b^2 - a^2}\) and \(b^2 - a^2 ≠ 0\), then \(b - a =\)

A. -1
B. 0
C. 1
D. 2
E. It cannot be determined from the information given.

_________________
New Project RC Butler 2019 - Practice 2 RC Passages Everyday
Final days of the GMAT Exam? => All GMAT Flashcards.
This Post Helps = Press +1 Kudos
Best of Luck on the GMAT!!

Originally posted by SajjadAhmad on 11 Dec 2018, 11:21.
Last edited by Bunuel on 12 Dec 2018, 01:33, edited 1 time in total.
Renamed the topic and edited the question.
Most Helpful Community Reply
Senior Manager
Senior Manager
User avatar
P
Joined: 15 Feb 2018
Posts: 258
Premium Member
Re: If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =  [#permalink]

Show Tags

New post 18 Jan 2019, 01:25
5
I feel like the above explanations skip steps.

\(a−b=\frac{(a−b)(a+b)}{(b−a)(b+a)}\)

(a+b)=(b+a), so we cancel each in the numerator and denominator

\(a−b=\frac{(a−b)}{(b−a)}\)

We have (a-b) on the left and in the numerator, so we can divide both sides by (a-b)

\(1=\frac{1}{(b−a)}\)

And multiply both sides by (b-a)

(b-a)=1/1=1
General Discussion
NUS School Moderator
User avatar
V
Joined: 18 Jul 2018
Posts: 987
Location: India
Concentration: Finance, Marketing
WE: Engineering (Energy and Utilities)
Premium Member Reviews Badge CAT Tests
Re: If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =  [#permalink]

Show Tags

New post 11 Dec 2018, 22:57
2
\(a - b = \frac{(a^2−b^2)}{(b^2−a^2)}\) = \(\frac{(a+b)(a-b)}{(b+a)(b-a)}\)
Multiplying by -1, gives
b - a = \(\frac{(a+b)(b-a)}{(b+a)(b-a)}\) = 1.

C is the answer.
_________________
Press +1 Kudos If my post helps!
Senior Manager
Senior Manager
User avatar
S
Joined: 12 Sep 2017
Posts: 298
If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =  [#permalink]

Show Tags

New post 07 Jan 2019, 20:39
Afc0892 wrote:
\(a - b = \frac{(a^2−b^2)}{(b^2−a^2)}\) = \(\frac{(a+b)(a-b)}{(b+a)(b-a)}\)
Multiplying by -1, gives
b - a = \(\frac{(a+b)(b-a)}{(b+a)(b-a)}\) = 1.

C is the answer.


Hello Afc0892

Could you please explain to me how I multiply by -1 the second term (right term)?

b - a = \(\frac{(a+b)(b-a)}{(b+a)(b-a)}\) = 1.

Kind regards!
NUS School Moderator
User avatar
V
Joined: 18 Jul 2018
Posts: 987
Location: India
Concentration: Finance, Marketing
WE: Engineering (Energy and Utilities)
Premium Member Reviews Badge CAT Tests
Re: If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =  [#permalink]

Show Tags

New post 07 Jan 2019, 20:50
jfranciscocuencag wrote:
Afc0892 wrote:
\(a - b = \frac{(a^2−b^2)}{(b^2−a^2)}\) = \(\frac{(a+b)(a-b)}{(b+a)(b-a)}\)
Multiplying by -1, gives
b - a = \(\frac{(a+b)(b-a)}{(b+a)(b-a)}\) = 1.

C is the answer.


Hello Afc0892

Could you please explain to me how I multiply by -1 the second term (right term)?

b - a = \(\frac{(a+b)(b-a)}{(b+a)(b-a)}\) = 1.

Kind regards!


Hey jfranciscocuencag, Sure I'll. :)

The question is asking for us to find the value of b-a. As you can see, we have found the value of a-b. On the RHS, a+b can be cancelled from both the numerator and the denominator. We are left with a-b/b-a. If we multiply both LHS and RHS by -1. Then RHS will be -(a-b)/(b-a)
= -a+b/b-a = b-a/b-a. Also, LHS will be -(a-b) = -a+b or b-a. Hence b-a = 1.

Hope this helps. :)

Posted from my mobile device
_________________
Press +1 Kudos If my post helps!
VP
VP
avatar
G
Joined: 09 Mar 2018
Posts: 1002
Location: India
If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =  [#permalink]

Show Tags

New post 07 Jan 2019, 20:55
1
SajjadAhmad wrote:
If \(a - b = \frac{a^2 - b^2}{b^2 - a^2}\) and \(b^2 - a^2 ≠ 0\), then \(b - a =\)

A. -1
B. 0
C. 1
D. 2
E. It cannot be determined from the information given.


So 2 things to remember,
\(a^2 - b^2\)= (a-b) (a+b)
\(b^2 - a^2\)= (b-a) (b+a)

With that in mind just substitute the values
\(a - b = \frac{a^2 - b^2}{b^2 - a^2}\)
\(a - b = \frac{(a-b) (a+b)}{(b-a) (b+a)}\)
b - a = 1

Correct Answer C
_________________
If you notice any discrepancy in my reasoning, please let me know. Lets improve together.

Quote which i can relate to.
Many of life's failures happen with people who do not realize how close they were to success when they gave up.
VP
VP
User avatar
D
Joined: 31 Oct 2013
Posts: 1393
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
Re: If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =  [#permalink]

Show Tags

New post 29 Jan 2019, 02:08
SajjadAhmad wrote:
If \(a - b = \frac{a^2 - b^2}{b^2 - a^2}\) and \(b^2 - a^2 ≠ 0\), then \(b - a =\)

A. -1
B. 0
C. 1
D. 2
E. It cannot be determined from the information given.



Given ,

\(a - b = \frac{a^2 - b^2}{b^2 - a^2}\)

\(a - b = \frac{a^2 - b^2}{-1(a^2 - b^2)}\)

a - b = -1

b - a = 1...........Multiplying both side by -1.

C is the correct answer.
GMAT Club Bot
Re: If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =   [#permalink] 29 Jan 2019, 02:08
Display posts from previous: Sort by

If a - b = (a^2 - b^2)/(b^2 - a^2) and b^2 - a^2 ≠ 0, then b - a =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne